A carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material and its preparation

By using carbon nanotube-enhanced carbon-coated porous silicon/alloy composite materials in lithium-ion batteries, the problem of poor circulation performance of silicon-based materials is solved, and high energy density and stable electrochemical performance are achieved.

CN118693272BActive Publication Date: 2024-12-31NINGBO HANGCHANG METAL MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411174917.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-31
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material, silicon-based materials, have poor circulation performance due to low conductivity and huge volume expansion during lithiation, making it difficult to meet the energy storage needs of new energy vehicle power batteries.

Method used

Using carbon nanotube-enhanced carbon-coated porous silicon/alloy composite material, nanoporous silicon is generated through magnesium nitride, and dispersed in aqueous citric acid solution. Combined with silicon alloy powder and surfactant, and carbonized by rolling and high temperature, it is formed. Carbon nanotube-enhanced carbon-coated porous silicon/alloy composites improve the conductivity and tap density of the material, and alleviate volume changes and charge transfer reactions.

Benefits of technology

It achieves high cycle stability and high first-term efficiency, improves the energy density of lithium-ion batteries, reduces side reactions on the electrode/electrolyte interface, and significantly improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118693272B_ABST
    Figure CN118693272B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and relates to a carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material and its preparation. The preparation method comprises: thermally nitriding nano magnesium silicon alloy powder, and then vacuum high temperature decomposing to obtain nano porous silicon powder; dispersing the nano silicon alloy powder in a citric acid aqueous solution, dispersing the nano silicon alloy powder, surfactant and sodium hydroxide in an aqueous solution, mixing and stirring the two solutions evenly, and drying to obtain a precursor; adding the precursor to softened asphalt, stirring evenly, and then rolling into a thin sheet by a roller press, cooling, crushing, and then high temperature carbonization, ball milling, sieving; and finally chemical vapor deposition. In the obtained carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material, the carbon-coated nano porous silicon and the nano silicon alloy are connected by carbon nanotubes and evenly dispersed in the carbon-coated shell; it has excellent electrochemical properties as a negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material and its preparation. Background Art

[0002] At present, commercial graphite, as the most common negative electrode material in lithium-ion batteries, can achieve a specific capacity that is very close to its theoretical capacity (372 mAh g -1 ), but this is far from meeting the market demand for new energy vehicle power batteries. In order to achieve a wider range of energy storage applications, it is necessary to explore new negative electrode materials with high theoretical specific capacity, such as silicon materials, which is the key to developing a new generation of high energy density lithium-ion batteries. However, due to the low conductivity of the silicon negative electrode and the huge volume expansion during the lithiation process, the poor cycle performance has seriously hindered the commercial application of silicon-based negative electrode materials. Therefore, researchers have developed various structural designs to adapt to the volume changes of silicon-based materials, as well as explored the combination of silicon and other materials to form a new type of negative electrode material system.

[0003] Among them, nano-sizing or alloying silicon is an effective strategy to improve the cycle stability of silicon negative electrodes. The use of special nanostructures and morphologies can effectively alleviate the breakage or pulverization of Si particles and shorten the diffusion distance of lithium ions, thereby improving the charge transfer reaction between silicon and lithium. However, the nanostructure itself also has some problems, such as easy agglomeration of nano-silicon powder, low tap density, and irreversible reactions at high specific surface areas, which greatly affect the electrochemical performance of the battery. By alloying silicon powder with other metals, such as aluminum, magnesium, iron, copper, tin, etc., not only the conductive properties of the metal are used to make up for the poor conductivity of silicon powder, but also the good ductility of the metal is used to alleviate the internal stress of the material during the lithium insertion and extraction process, thereby inhibiting the volume change of silicon. In addition, compared with pure silicon particles, the tap density of silicon alloy powder is higher, which is beneficial to increase the energy density of the battery cell, but silicon alloys have the defects of low specific capacity and first coulombic efficiency (for example, iron silicon <100mAh g -1 ). Therefore, when designing related negative electrode materials, not only the dispersion of nanopowders should be considered, but also the silicon content should be increased as much as possible to improve the specific capacity while maintaining cycle stability. Summary of the invention

[0004] In order to solve the above problems existing in the prior art, the purpose of the present invention is to provide a carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material and a preparation method thereof. Among them, the carbon-coated nanoporous silicon and the nano-silicon alloy are interconnected by carbon nanotubes and uniformly dispersed in the carbon-coated shell; the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material has high cycle stability and high initial efficiency as a negative electrode material, and can realize the energy storage application of high energy density lithium-ion batteries.

[0005] One object of the present invention is achieved by the following technical solutions:

[0006] A method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material comprises the following steps:

[0007] S1. thermally nitriding nano magnesium silicon alloy powder in nitrogen, and then heating at high temperature in vacuum to decompose and vaporize the generated magnesium nitride to obtain nano porous silicon (NPSi);

[0008] S2, dispersing nanoporous silicon in a citric acid aqueous solution to obtain solution 1; dispersing nano silicon alloy powder, a surfactant and sodium hydroxide in an aqueous solution to obtain solution 2; mixing solutions 1 and 2, stirring and drying to obtain a precursor;

[0009] S3, adding the precursor to the softened asphalt, stirring evenly to obtain a molten material; then rolling the molten material into a sheet by a roller press, and crushing it after cooling; in an inert atmosphere, high-temperature carbonizing the crushed material, ball milling, and sieving to obtain the NPSi@C-CNTs-MeSi composite material;

[0010] S4. The NPSi@C-CNTs-MeSi composite material is subjected to chemical vapor deposition in an inert atmosphere and a carbon source atmosphere to obtain a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material.

[0011] Preferably, the magnesium-silicon alloy powder in step S1 is MgSi x , where x=0.1~2.

[0012] Preferably, the average particle size of the nano magnesium-silicon alloy powder is 5 to 500 nm, more preferably 25 to 250 nm.

[0013] Preferably, the nitriding temperature of step S1 is 700-900° C., and the nitriding time is 3-12 hours.

[0014] Preferably, the high temperature heating temperature of step S1 is 900-1200° C., and the decomposition time is 1-6 hours.

[0015] Preferably, the silicon alloy in step S2 is an alloy composed of silicon and Me metal elements, and the molecular formula is MeSi x , wherein x=0.1~2, the Me metal element is one or more of Mg, Fe, Cu, and Ni, and the mass percentage of the Me metal element is 10~70wt%.

[0016] Preferably, the average particle size of the nano-silicon alloy powder in step S2 is 5 to 500 nm, and more preferably 10 to 80 nm.

[0017] Preferably, the concentration of citric acid in the citric acid aqueous solution is 0.5 to 500 g / L, more preferably 1 to 300 g / L.

[0018] Preferably, the mass ratio of the nanoporous silicon to citric acid is preferably 10-100:1, and more preferably 20-80:1.

[0019] Preferably, the mass ratio of the nanoporous silicon to the nano-silicon alloy powder is 0.2-5:1.

[0020] Preferably, the surfactant is at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide. The surfactant is added to slow down the agglomeration of the nanopowder.

[0021] Preferably, the mass ratio of the surfactant to the citric acid is 1:1-10.

[0022] Preferably, the mass of sodium hydroxide is 10-30% of the mass of citric acid.

[0023] Preferably, the stirring temperature of step S2 is 20-80° C., the stirring rate is 200-1500 rpm, the stirring time is 6-40 h, and the stirring is performed until the slurry becomes viscous.

[0024] Preferably, the drying temperature of step S2 is 70-120° C., and the drying time is 5-30 hours.

[0025] Preferably, the asphalt is heated and softened at a high temperature in a muffle furnace, and the softening temperature is 380-500°C.

[0026] Preferably, in step S3, the mass ratio of asphalt to precursor is 0.1-2:1.

[0027] Preferably, the stirring time of step S3 is 0.5-3 h, and the stirring speed is 100-800 rpm.

[0028] Preferably, the rolling parameters in step S3 include: a roller speed of 0.3-3 m / s, a roller gap of 1-5 mm, and continuous rolling for at least 2 times.

[0029] Preferably, the flakes in step S3 are crushed to a particle size of ≤5 mm.

[0030] Preferably, the inert atmosphere is one or both of an argon atmosphere and a nitrogen atmosphere.

[0031] Preferably, the high temperature carbonization conditions in step S3 include: a heating rate of 0.5-10° C. / min, a carbonization temperature of 700-1000° C., and a carbonization time of 0.5-5 h.

[0032] Preferably, the ball milling conditions in step S3 include: a ball milling speed of 150-500 r / min, and a ball milling time of 0.5-2 h.

[0033] Preferably, the sieving mesh number in step S3 is 100-800 meshes.

[0034] Preferably, in step S4, the carbon source atmosphere is one or more of acetylene, methane, ethanol, and ethylene. The gas flow rate of the carbon source atmosphere is 50-600 sccm, and the gas flow rate of the inert atmosphere is 400-800 sccm. The reaction gas pressure is 300-700 Pa.

[0035] Preferably, the chemical vapor deposition conditions in step S4 include: a heating rate of 1-10° C. / min, a temperature of 800-1000° C., and a time of 0.5-5 h.

[0036] The second object of the present invention is achieved by the following technical solutions:

[0037] The preparation method mentioned above prepares a carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material.

[0038] The third object of the present invention is achieved by the following technical solutions:

[0039] The carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material is used in a lithium-ion battery. The negative electrode sheet of the lithium-ion battery comprises the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material.

[0040] Preferably, the raw materials including the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material are mixed with a solvent to prepare a slurry, which is coated on a current collector and dried to obtain a negative electrode sheet.

[0041] Preferably, the raw material includes the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material and a binder; the mass ratio of the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material and the binder is (89~98):(2~11).

[0042] Preferably, the raw materials include the carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material, a conductive agent and a binder; the mass ratio of the carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material, the conductive agent and the binder is (87~97): (0.5~5): (2~10).

[0043] The conductive agent, binder and solvent are all commonly used substances in the preparation process of negative electrode sheets and are not particularly limited here.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. In the present invention, nanoporous silicon (NPSi) is prepared using magnesium silicon alloy powder as raw material. First, liquid Mg3N2 and solid Si are generated in situ during nitrogen nitridation, and magnesium nitride is decomposed and evaporated in a subsequent vacuum high-temperature environment to form NPSi material. The pore structure (such as pore size and porosity, etc.) of porous silicon can be easily controlled by adjusting the magnesium content and nitridation temperature, laying the foundation for subsequent structural design. In addition, the generated magnesium vapor can be recovered by condensation, and the nitrogen can be recycled, which greatly reduces the loss of materials and is more green and economical.

[0046] 2. The present invention uses citric acid to modify nanoporous silicon particles, which can remove residual magnesium nitride impurities in porous silicon on the one hand; on the other hand, citric acid, as a carbon source, has a low carbonization temperature so that it will be carbonized during the asphalt stirring process, first forming an amorphous carbon layer on the surface of NPSi, and a large amount of gas overflows, and a porous structure is also formed in the asphalt matrix, which further alleviates the volume expansion effect. In addition, the presence of citrate ions enhances the negative charge density on the surface of porous silicon, so that the silicon alloy powder added later can be evenly dispersed around the nanoporous silicon particles under the electrostatic interaction of the cationic surfactant.

[0047] 3. The silicon alloy powder used in the present invention can not only improve the conductivity and tap density of the material, but also serve as a catalyst for the growth of carbon nanotubes. For example, the Fe, Ni and other elements in the silicon alloy powder can serve as active sites to convert the carbonization products of citric acid and asphalt into carbon nanotubes, which can effectively anchor Si particles and prevent the agglomeration effect of nanoporous silicon powder.

[0048] 4. The carbon nanotubes (CNTs) catalytically generated on the surface of the silicon alloy in the present invention serve as enhanced stress buffers inside the core-shell, not only supporting a stable carbon framework to accommodate large Si volume changes during lithium insertion / delithiation, but also providing a high electron transmission channel between nano-silicon particles and electrodes, which is crucial for the good utilization of active materials.

[0049] 5. The present invention uses a roller press to roll the mixture of NPSi@CA-MeSi precursor and molten asphalt to form a thin sheet material. Because the viscosity of asphalt is relatively high in a high-temperature molten state, it is difficult to stir evenly. The roller press is required to generate a greater mechanical force to further disperse the various components of the material evenly. In addition, the pressed thin sheet can be cooled more quickly and is easier to perform the subsequent crushing process.

[0050] 6. The outermost CVD-coated carbon layer in the present invention reduces the BET surface area, limits the direct contact between Si and the organic electrolyte, and further generates a stable SEI layer, reducing unnecessary side reactions at the electrode / electrolyte interface, thereby improving the primary efficiency of the negative electrode material.

[0051] 7. The carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material prepared in the present invention is applied as a negative electrode material to a lithium-ion battery and shows high specific capacity, first coulombic efficiency and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 A schematic diagram of the structure of the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material provided by the present invention;

[0053] Figure 2 The scanning electron microscope image (a) of the material obtained in step (3) of Example 1 of the present invention and the scanning electron microscope image (b) of the carbon-coated NPSi@C-CNTs-FeSi2 composite material prepared in step (5);

[0054] Figure 3 is an X-ray diffraction pattern of the carbon-coated NPSi@C-CNTs-FeSi2 composite material in Example 1 of the present invention;

[0055] Figure 4 The first three charge-discharge curves of the carbon-coated NPSi@C-CNTs-FeSi2 composite material used as a lithium-ion negative electrode material in Example 1 of the present invention;

[0056] Figure 5 This is a cycle performance curve of a lithium-ion battery assembled with the carbon-coated NPSi@C-CNTs-FeSi2 composite negative electrode material in Example 1 of the present invention. DETAILED DESCRIPTION

[0057] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art. Example 1

[0058] The preparation method of the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material of this embodiment comprises the following steps:

[0059] (1) 1 kg of magnesium-silicon alloy powder with an average particle size of 200 nm was placed in a rotary furnace and heated at 800°C for 6 h in a nitrogen atmosphere for nitridation treatment to obtain a Si / Mg3N2 composite material; it was then heated in vacuum at 900°C for 3 h to obtain a nanoporous silicon (NPSi) material.

[0060] (2) Dissolve 13.5g of citric acid (CA) in 1000mL of pure water, add 350g of nanoporous silicon powder, and stir at 25°C and 1000rpm for 30min to obtain solution 1. Disperse 150g of iron-silicon alloy powder (Fe mass fraction is 10%) with an average particle size of 50nm in 1000mL of pure water, add 5g of hexadecyltrimethylammonium bromide and 3g of sodium hydroxide in turn, and stir for 30min under the same conditions to obtain solution 2. Mix solutions 1 and 2, heat and stir at 70°C and 350rpm for 24h until the slurry becomes viscous. Dry the evenly dispersed slurry in an oven at 100°C for 12h to obtain NPSi@CA-FeSi2 precursor.

[0061] (3) 600 g of asphalt was melted and softened in a muffle furnace at 400 °C, and then 500 g of NPSi@CA-FeSi2 precursor was gradually and slowly added, and stirred at 300 rpm for 1 h at 400 °C until the two were evenly mixed; the molten material was roller pressed using a three-axis linkage roller press at a speed of 1 m / s and a roller gap of 2 mm for 3 times to obtain a thin flake. After the thin flake material was cooled, it was crushed by a jaw crusher with a particle size range of 0.1~5 mm.

[0062] (4) Under the protection of argon atmosphere, the above materials were placed in a tube furnace and heated at a heating rate of 1°C / min, and kept at 300°C for 30min, and then continued to heat to 750°C and kept for 1h for high-temperature carbonization. After cooling to room temperature, the materials were placed in a high-energy ball mill for ball milling. The ball milling setting parameters were: speed 420r / min, 200g of 20mm zirconium balls, 400g of 12mm zirconium balls, and time 30min. The ball-milled sample was passed through a 625-mesh molecular sieve to obtain a NPSi@C-CNTs-FeSi2 composite material with a particle size of about 20μm.

[0063] (5) The sieved composite material was placed in a rotary furnace for chemical vapor deposition coating, wherein the coating process parameters were set as follows: heating rate of 1°C / min, reaction temperature of 850°C, reaction time of 2h, argon, methane and acetylene, gas flow rates of 500, 50, and 350sccm, respectively, and reaction pressure of 500Pa to obtain a carbon-coated NPSi@C-CNTs-FeSi2 composite material.

[0064] Figure 1 The carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material (carbon-coated NPSi@C-CNTs-MeSi x) structure diagram: a carbon coating is formed on the surface of nanoporous silicon particles, NPSi@C particles and nano-silicon alloys are connected to each other through carbon nanotubes derived from citric acid and asphalt, NPSi@C-CNTs-MeSi x The surface of the composite material is then coated with a layer of amorphous carbon to form the final carbon-coated NPSi@C-CNTs-MeSi x .

[0065] The SEM image of the composite material of the NPSi@CA-FeSi2 precursor prepared in Example 1 after being stirred with asphalt, rolled and crushed is shown in FIG. Figure 2 As shown in (a), it can be seen that the larger particles with rough surfaces are NPSi@C, and the smaller particles with dull colors and smooth surfaces are nano-iron-silicon alloy powders. The two are mixed and evenly dispersed on the asphalt matrix. At the same time, there are a large number of pore structures, which is mainly due to the carbonization of the coated organic layer during the high-temperature stirring process, resulting in a large amount of gas overflow. In addition, Figure 2 As shown in (b), the SEM image of the carbon-coated NPSi@C-CNTs-FeSi2 composite material prepared in Example 1 shows that after high-temperature carbonization and CVD coating, a large number of carbon nanotubes with buffering effects exist inside the outermost carbon shell, and the NPSi@C particles and nano-iron-silicon alloy powder are interconnected. The composite material obtained in this example was tested by X-ray diffraction technology, and the spectrum is shown in Figure 3 As shown, it shows that there are mainly diffraction peaks of crystalline silicon, amorphous carbon and FeSi2 phase. The silicon content measured by energy dispersive X-ray spectrometer accounts for 52.7% of the total mass of the composite material, which is close to the theoretical designed Si / C mass ratio (1:1). Example 2

[0066] The difference between Example 2 and Example 1 is that the mass fraction of Fe in the iron-silicon alloy powder of Example 2 is 20%, and the rest is the same as Example 1. Example 3

[0067] The difference between Example 3 and Example 1 is that Example 3 uses copper-silicon alloy powder (wherein the mass fraction of copper is 10%) to replace the iron-silicon alloy powder of Example 1, and the rest is the same as Example 1. Example 4

[0068] The difference between Example 4 and Example 1 is that the average particle size of the magnesium-silicon alloy powder in Example 4 is 50 nm, and the rest is the same as Example 1. Example 5

[0069] The difference between Example 5 and Example 1 is that the amount of asphalt added in Example 5 is 500g, and the rest is the same as Example 1. Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses 350 g of silicon powder with an average particle size of 200 nm to replace the nanoporous silicon powder in Example 1, and the subsequent process is the same as that in Example 1. Comparative Example 2

[0071] The difference between Comparative Example 2 and Example 1 is that the CVD coating process in step (3) is not performed in Comparative Example 2, and the rest is the same as Example 1. Comparative Example 3

[0072] The difference between Comparative Example 3 and Example 1 is that step (2) of Comparative Example 3 is:

[0073] Dissolve 13.5g of citric acid (CA) in 2000mL of pure water, add 500g of nanoporous silicon, stir at 25°C and 1000rpm for 30min, then add 5g of hexadecyltrimethylammonium bromide and 3g of sodium hydroxide in sequence. Continue stirring under the same conditions for 30min, then heat and stir at 70°C and 350rpm for 24h until the slurry becomes viscous. Dry the evenly dispersed slurry in an oven at 100°C for 12h to obtain the NPSi@CA precursor.

[0074] The subsequent steps are the same as those in Example 1. Comparative Example 4

[0075] The difference between Comparative Example 4 and Example 1 is that step (2) of Comparative Example 4 is:

[0076] 350g of nanoporous silicon powder was dispersed in 1000mL of pure water and stirred at 25°C and 1000rpm for 30min to obtain solvent 1. 150g of iron-silicon alloy powder (Fe mass fraction is 10%) with an average particle size of 50nm and 5g of hexadecyltrimethylammonium bromide were dispersed in 1000ml of pure water to obtain solution 2. Solutions 1 and 2 were mixed and heated and stirred at 70°C and 350rpm for 24h until the slurry became viscous. The uniformly dispersed slurry was dried in an oven at 100°C for 12h to obtain NPSi-FeSi2 precursor.

[0077] The subsequent steps are the same as those in Example 1. Comparative Example 5

[0078] The difference between Comparative Example 5 and Example 1 is that 13.5 g of sucrose is added in Comparative Example 5 to replace the citric acid in Example 1, and the rest is the same as Example 1. Comparative Example 6

[0079] The difference between Comparative Example 6 and Example 1 is that step (3) of Comparative Example 6 is:

[0080] 600 g of asphalt was melted and softened in a muffle furnace at 400 °C, and then 500 g of NPSi@CA-FeSi2 precursor was gradually and slowly added, and stirred at 300 rpm at 400 °C for 1 hour until the two were evenly mixed; after cooling, it was crushed by a jaw crusher with a particle size range of 0.1~5 mm.

[0081] The remaining steps are the same as those in Example 1.

[0082] The composite materials prepared in Examples 1-5 and Comparative Examples 1-6, Super P, single-walled carbon nanotubes (SWCNT), polyacrylic acid (PAA) and SBR were added to deionized water in a ratio of 94.55:1:0.15:1.3:3, stirred and mixed to form a uniform slurry, coated on copper foil, dried in a vacuum drying oven at 110°C for 12 hours, and then cut into negative electrode sheets with a diameter of 14 mm. After assembling into button cells using a metal lithium sheet as a counter electrode, PE as a diaphragm, and a 1M LiPF6 solution dissolved in ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as an electrolyte, conventional electrochemical performance tests and four-probe powder resistance tests were performed, and the results are shown in Table 1.

[0083] Table 1 Test results of Examples 1 to 5 and Comparative Examples 1 to 6

[0084]

[0085] According to the data in the table and the accompanying drawings, the carbon-coated NPSi@C-CNTs-FeSi2 composite negative electrode material prepared in Example 1 of the present invention has relatively excellent electrochemical performance in terms of comprehensive specific capacity, first efficiency and cycle performance. The powder resistance test shows that the powder resistivity of the composite material is 3.115Ω·cm under a pressure of 4kN and 1.053Ω·cm under a pressure of 20kN. In the electrochemical performance test in lithium-ion batteries, Figures 4 and 5 As shown, at a rate of 0.1C, the first charge and discharge specific capacities of the carbon-coated NPSi@C-CNTs-FeSi2 composite material of Example 1 are 1713.7mAh / g and 1475.5mAh / g, respectively, with a first efficiency of up to 86.1%; in addition, the capacity retention rate is 92.3% after 100 cycles at a high current density of 1C.

[0086] Compared with Example 1, in Example 2, due to the increase in the relative content of iron, although more CNTs buffer layers can be generated, the cycle stability is better, but this leads to a significant decrease in the specific capacity of the material. In Comparative Example 1, solid nano-silicon is used to replace porous silicon, which greatly reduces the three-dimensional interconnected nanopores, which is not conducive to regulating the volume expansion of silicon. In Comparative Example 2, the outermost coated carbon layer is missing, so that it has relatively poor first effect and cycle stability. In Comparative Example 3, there is a lack of silicon alloy powder, there is no CNTs buffer layer, and only a three-level coated silicon-carbon composite material is obtained, so that its powder resistivity is high and the conductivity is poor. In addition, the nanoporous silicon powder of the material is easy to agglomerate, which has a harmful effect on the transport properties of the electrode. In Comparative Example 4, the nanoporous silicon powder loses a layer of carbon coating, which makes the cycle stability limited. In Comparative Example 5, sucrose is used instead of citric acid. Since the electronegativity of the carboxyl group is greater than that of the hydroxyl group, the dispersing effect of citric acid on nanoporous silicon powder is better than that of sucrose on porous silicon powder, which ultimately makes the electrochemical performance of the composite material slightly lower than that of Example 1. Comparative Example 6 was not subjected to roller pressing treatment, and the nanoporous silicon powder and silicon alloy were unevenly distributed, which affected the growth of carbon nanotubes and thus the electrochemical performance.

[0087] In summary, the present invention can prepare a lithium ion negative electrode material with high capacity, high initial efficiency and long cycle life.

[0088] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0089] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0090] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material, characterized in that: The following steps are involved: S1, thermally nitriding the nano magnesium silicon alloy powder in nitrogen, and then heating it at high temperature in vacuum to decompose and vaporize the generated magnesium nitride to obtain nano porous silicon; S2, dispersing nanoporous silicon in a citric acid aqueous solution to obtain solution 1; Dispersing nano silicon alloy powder, surfactant and sodium hydroxide in an aqueous solution to obtain solution 2; mixing solutions 1 and 2, stirring and drying to obtain a precursor; S3, adding the precursor to the softened asphalt, stirring evenly to obtain a molten material; then rolling the molten material into a sheet by a roller press, and crushing it after cooling; in an inert atmosphere, high-temperature carbonizing the crushed material, ball milling, and sieving to obtain the NPSi@C-CNTs-MeSi composite material; S4, chemical vapor deposition of the NPSi@C-CNTs-MeSi composite material under an inert atmosphere and a carbon source atmosphere to obtain a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material; The silicon alloy in step S2 is an alloy composed of silicon and Me metal elements, and its molecular formula is MeSi x , wherein x=0.1~2, the Me metal element is one or more of Mg, Fe, Cu, and Ni, and the mass percentage of the Me metal element is 10~70wt%.

2. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: The nitriding temperature in step S1 is 700-900°C, and the nitriding time is 3-12h; The high temperature heating temperature of step S1 is 900-1200°C, and the decomposition time is 1-6h; The average particle size of the nano magnesium-silicon alloy powder in step S1 is 5-500 nm.

3. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: The average particle size of the nano-silicon alloy powder is 5-500nm.

4. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: In the citric acid aqueous solution of step S2, the concentration of citric acid is 0.5-500 g / L; The mass ratio of the nanoporous silicon to the citric acid is 10-100:1; The mass ratio of the nanoporous silicon to the nano-silicon alloy powder is 0.2-5:1; The surfactant is at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium bromide; The mass ratio of the surfactant to citric acid is 1:1-10; The mass of sodium hydroxide is 10~30% of the mass of citric acid.

5. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: The stirring temperature of step S2 is 20-80° C., the stirring rate is 200-1500 rpm, and the stirring time is 6-40 h; The drying temperature of step S2 is 70-120° C., and the drying time is 5-30 hours.

6. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: In step S3, the mass ratio of asphalt to precursor is 0.1-2:1; The asphalt is heated and softened in a muffle furnace at a temperature of 380~500℃; The stirring time of step S3 is 0.5-3h, and the stirring speed is 100-800rpm; The rolling parameters in step S3 include: a roller speed of 0.3-3 m / s, a roller gap of 1-5 mm, and continuous rolling times of at least 2 times; The flakes in step S3 are crushed to a particle size of ≤5 mm.

7. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: The conditions for high temperature carbonization in step S3 include: a heating rate of 0.5-10°C / min, a carbonization temperature of 700-1000°C, and a carbonization time of 0.5-5h; The ball milling conditions in step S3 include: a ball milling speed of 150-500 r / min, and a ball milling time of 0.5-2 h; The sieving mesh number in step S3 is 100-800 meshes.

8. The method for preparing a carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material according to claim 1, characterized in that: In step S4, the carbon source atmosphere is one or more of acetylene, methane, ethanol, and ethylene; The gas flow rate of the carbon source atmosphere is 50~600sccm, the gas flow rate of the inert atmosphere is 400~800sccm, and the reaction gas pressure is 300~700Pa; The conditions for chemical vapor deposition in step S4 include: a heating rate of 1-10° C. / min, a temperature of 800-1000° C., and a time of 0.5-5 h.

9. A carbon nanotube-reinforced carbon-coated porous silicon / alloy composite material prepared by the preparation method according to claim 1.

10. The use of a carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material in a lithium-ion battery according to claim 9, characterized in that: The negative electrode sheet of the lithium ion battery comprises the carbon nanotube-enhanced carbon-coated porous silicon / alloy composite material.

Citation Information

Cited By

  • Preparation device and method of carbon nanotube coated porous silicon structure

    CN120984547A

  • Preparation device and method of carbon nanotube coated porous silicon structure

    CN120984547B